Antibacterial and Antioxidant Activity of extract and fractions of Lonicera nummularifolia Jaub & Spach - Mohammad Ali Farboodniay Jahromi; Amir Emami; Raha Nazeri; Neda Pirbonyeh (Shiraz University of Medical Sciences, 2020)
The present study deals with antibacterial and antioxidant screening of ethanolic leaf extract and various fractions of Lonicera nummularifolia, an endemic plant of Caprifoliace family. The ethanolic extract was prepared using soxhlet extraction procedure and fractionation of extract was performed by a continuous liquid-liquid extraction method. Total phenol, flavonoid and triterpenoid were determined in the extract using standard spectrophotometric methods. Antioxidant assays including DPPH and FRAP were conducted in order to evaluate the antioxidant capacity. Antibacterial activity of total ehanolic extract and fractions were evaluated by measuring MIC (Minimum Inhibitory Concentration) and MBC (Minimum Bactericidal Concentration) against four standard bacterial strains, including Escherichia Coli, Staphylococcus ureus, Pseudomonas aeroginosae and Acenitobacter baumannii. using broth micro-dilution method. Total phenol content of hydroalcoholic extract was found to be higher than flavonoid. Results of antioxidant assays indicated that ferric reducing antioxidant power of the extract was promising. Results of antibacterial screening declared the lowest MIC value for ethanol extract and therefore higher bacteriostatic activity against the tested bacterial strains compare to chloroform and ethyl acetate fractions. Ethanolic extract also revealed significant bactericidal activity among all the tested extracts. Overall inspection of the results declared moderate DPPH free radical scavenging, ferric reducing activity and antibacterial properties of L. nummularifolia which is worthy of further thorough investigations. Isolation and characterisation of active substances of the extract are interesting approaches in order to validate antibacterial and ferric reducing properties of the plant.